2019
DOI: 10.1097/mjt.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Value of Cystatin C–Based e-GFR Measurements to Predict Long-Term Tenofovir Nephrotoxicity in Patients With Hepatitis B

Abstract: Long-term tenofovir disoproxil fumarate nephrotoxicity can be predicted by serum cystatin C plus creatinine-based e-GFR measured before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The eGFRs of patients treated with TDF decreased in a time-dependent manner, whereas those of patients treated with ETV increased or decreased across various time points. 15 , 16 , 20 , 23 , 24 , 28 Similar percentage of patients in both the treatment groups showed ≥20% decrease in eGFR during the treatment (based on CG, TDF 35.0% vs ETV 36.3%; based on MDRD, TDF 41.3% vs ETV 43.8%). 33 A similar tendency was also observed in a recent clinical trial conducted in Thailand.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The eGFRs of patients treated with TDF decreased in a time-dependent manner, whereas those of patients treated with ETV increased or decreased across various time points. 15 , 16 , 20 , 23 , 24 , 28 Similar percentage of patients in both the treatment groups showed ≥20% decrease in eGFR during the treatment (based on CG, TDF 35.0% vs ETV 36.3%; based on MDRD, TDF 41.3% vs ETV 43.8%). 33 A similar tendency was also observed in a recent clinical trial conducted in Thailand.…”
Section: Discussionmentioning
confidence: 86%
“…A prospective cohort study conducted in Turkey reported a change in eGFR in 44 patients with TDF and 32 patients with ETV according to the Chronic Kidney Disease Epidemiology Collaboration and cystatin C (CKD-EPI-CysC) method. 16 The mean eGFR in the patients with TDF decreased from 84.7 mL/min/1.73 m 2 at BL to 76.9 mL/min/1.73 m 2 at 24 months ( p =0.004) and that in the patients with ETV decreased from 90.0 mL/min/1.73 m 2 at BL to 84.5 mL/min/1.73 m 2 at 24 months ( p =0.46). However, the mean values of eGFR in both groups were different when the Chronic Kidney Disease Epidemiology Collaboration and creatinine plus cystatin C (CKD-EPI-Cr-CysC) method was used.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, CHB patients with cirrhosis are more likely to develop renal insu ciency, including acute kidney injury or hepatorenal syndrome, due to reduced renal blood ow and hemodynamic disturbances [10]. Furthermore, renal tubular dysfunction and Fanconi syndrome have been associated with TDF therapy for a decade [11][12][13]. Subsequently, several studies have reported the comparative analyses of renal function between patients receiving ETV and TDF; however, these studies had small sample sizes [14,15] and short follow-up periods [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Cys C serum levels also increased in cigarette smoking, cancer, neurological, and atherosclerosis. [27]…”
Section: Biomarkers Of Nephrotoxicitymentioning
confidence: 99%